Heavy metals in essential oils proposed for the modification of footwear lining leather—Quality management and product safety - Elżbieta Bielak (PLoS ONE, 2025)
Due to their antiseptic action, essential oils can be incorporated into leather in order to improve the hygienic properties of footwear by reducing microbial growth and multiplication in the interior. This paper presents the results of analyses of the contents of heavy metals, i.e., As, Cd, Cu, Ni and Pb in cinnamon, eucalyptus, oregano, manuka and thyme oils proposed for modification of lining leather. Experiments carried out using atomic absorption spectrometry were designed to evaluate the impact of the addition of these oils on the quality and safety of footwear considering the possible presence of toxic metals. In the context of the limits for metal contents in products set out in the European REACH Regulation, Oeko-Tex® Leather Standard by Oeko-Tex® Association, Restricted Substances List by AFIRM Group and List of Restricted Substances in Shoes by CADS Association, it was found that the oils tested were characterised by low levels of As (thyme, oregano and eucalyptus oils: not detected, other oils: 0.002 mg/kg – 0.015 mg/kg), Cd (0.001 mg/kg – 0.022 mg/kg), Cu (0.06 mg/kg – 0.184 mg/kg), Ni (0.025 mg/kg – 0.144 mg/kg) and Pb (0.06 mg/kg – 0.097 mg/kg). Therefore, their application to lining leather should not impair the quality of footwear understood in terms of its safety for the user. Given the limited number of analyses of heavy metal contents in essential oils of various applications, in the context of the study conducted, which, although in small numbers, nevertheless confirmed the presence of metals in oils, it was concluded that such analyses should be conducted on a larger scale. In order to ensure the quality and safety of products enriched with essential oils, it is necessary to continuously monitor an important property of essential oils, namely their content of harmful heavy metals.